Variationsrechnung: 25.6. bis 1.7.1978 - Heinz, Erhard; Hildebrandt, Stefan; Jäger, Willi (Tagungsbericht, 1978)
H.-W. Alt, Heidelberg; J. F. G. Auchmuty, Bloomington; M. Beeson, Bonn; R. Böhme, Erlangen; G. Dziuk, Aachen; J. Eells, Coventry; G. Eisen, Bonn; H. Engler, Heidelberg; R. Finn, Stanford; J. Frehse, Bonn; C. Gerhardt, Heidelberg; M. Giaquinta, Ferrera; M. Grüter, Düsseldorf; R. Gulliver, Minneapolis; E. Heinz, Göttingen; S. Hildebrandt, Bonn; E. Hölder, Mainz; W. Jäger, Heidelberg; H. Kaul, Duisburg; N. Kilimann, Bayreuth; M. König, München; M. Kucera, Prag; R. Landes, Bonn; L. Lemaire, Brüssel; F. Lewerenz, Göttingen; S. Luckhaus, Heidelberg; K. Maurin, Warschau; M. Meier, Bonn; D. Müller, Göttingen; J. Necas, Prag; J. C. C. Nitsche, Minneapolis; H. Pecher, Wuppertal; M. Reeken, Bochum; Sacks, Chicago; G. C. Simader, Bayreuth; K. Schüffler, Düsseldorf; L. Simon, Minneapolis; S. Spagnolo, Pisa; E. Sperner, Bayreuth; K. Steffen, Düsseldorf; G. Ströhmer, Aachen; G. Talenti, Florenz; E. Tausch, Bonn; F. Tomi, Saarbrücken; A. J. Tromba, Santa Cruz; K. Uhlenbeck, Chicago; W. von Wahl, Bayreuth; M. Wiegner, Bochum